Improvement of Breastfeeding Efficacy Through Small Group Education of Cadres with Pregnant Women - Epti Yorita; Sri Yanniarti; Yulinda Yulinda; Rina Rina; Rialike Burhan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
WHO recommends that every infant should be exclusively breastfed, but until now the coverage of exclusive breastfeeding is still low due to factors such as knowledge, breastfeeding efficacy, family support, lactation problems, and barriers in the health care system. This study aims to determine the effectiveness of Small group education of cadres with pregnant women on breastfeeding efficacy among third trimester pregnant women on Enggano Island. The research design was a quasi-experimental pre-test and post-test with a control group. The treathird trimesterent group was pregnant women who received Small group education of cadres with pregnant women while the control group was pregnant women who received conventional education. The study was conducted at Enggano Health Centre from January to November 2023 with a sample of 50 pregnant women in the third trimester of pregnancy from 25-36 weeks of age, selected by purposive sampling. The research instruments were modules and leaflets on exclusive breastfeeding, developed through a needs assessment, while breastfeeding efficacy was measured using the Breastfeeding Self-efficacy Scale-Short Form (BSES-SF). Data were analysed univariate, bivariate with wilcoxon and multivariate with spearman rank test. The results showed that there was an effect of Small group education of cadres with pregnant women class education on breastfeeding effectiveness with p=0.00 mean difference of 19.56. There was an effect of conventional class education on breastfeeding effectiveness in the control group with p=0.46 mean difference of 1.12. The class was more effective in improving breastfeeding practices among pregnant women with p=0.00 mean difference of 47.26. Class and education level were the most dominant factors in improving breastfeeding efficiency among pregnant women. The conclusion of this study is that the small group education of cadre with pregnant women is effective in improving breastfeeding efficacy in pregnant women in the third trimester. Keywords: Breastfeeding, Education, Efficacy, Small Group